The Tendency Towards the Narrative in the Babylonian Talmud: Halakhah, Aggadah, and Historical Image - Marienberg-Millikowsky, Itay (Jewish Thought, 2022)
This article discusses the stories of the Babylonian Talmud from the point of view proposed by the literary researcher Franco Moretti by pointing out the problem of “the great unread”; that is, all the immense literary material that for various reasons has escaped research attention, which, if only it had been taken into account, might have made the accepted literary history completely different. Eventually, this problem can lead to the use of computational tools (as happened for Moretti, as well as for the present author), but, as this article emphasizes, before choosing this solution, it is imperative that we dwell on the problem itself. Among the many stories of the Babylonian Talmud, it is argued here, a relatively small group of stories was canonized, while many others remained on the margins of the research discourse, either because they did not fit into the accepted genre frameworks of Talmudic literature, because their level of narrativity turned out to be too low, or because their role in organizing the Talmudic Sugya prevented researchers from seeing them as stories in the full sense of the word. These phenomena, as well as many others, are all consequences of the rise of narrativity as an integral part of the Babylonian Talmud and as the factor that shapes it as a whole, sometimes manifested in developed and polished stories, but at other times having a relatively minor impact. “The great unread” of the Babylonian Talmud is thus to be found more than anything in what makes this Talmud what it is (at least from a literary point of view): a composition with a continuous, infrastructural narrative quality whose expression goes far beyond what is to be found in the corpus of those stories that have mostly occupied researchers. In the article, the implications of this claim are examined in two complementary contexts: how narrativity affects halachic discourse, and how it affects the image of the Babylonian Beit Midrash.